KUALITAS PELAYANAN PADA PERPUSTAKAAN DAERAH KOTA SALATIGA - Elisa Irawati; Tri Widodo (Among Makarti, 2019)
AbstractThis research was conducted to determine the quality of service at the regional library in Salatiga. Primary data was obtained by distributing questionnaires to respondents, namely visitors at the Salatiga city library. The population in this study were 295,860 visitors and the sample in this study were 100 respondents who were students of STIE AMA, IAIN and SWCU Salatiga. The analysis used included multiple linear regression analysis, t test and F test. Based on the results of data analysis, the results of the study can be explained as follows: validity and reliability test shows that the count of each item> r-table (0.1946) and the value of Cronbach's Alpha each research variable> 0.6 so that the research declared valid and reliable. While the results of service satisfaction testing in the Salatiga city library were proven by adjusted R Square in this study of 0.385, which means that 38.5% of the satisfaction variables can be explained by five independent variables tangible, empathetic, reliability, responsiveness and assurance. While the remaining 61.5% is explained by other reasons outside the model. Test F obtained F count 13,396 probability 0,000. because the probability <0.05, the regression model can be said that tangible, empathetic, reliability, responsiveness and assurance together have an effect on satisfaction. The t test shows that tangible and emphaty variables have a significance value of <0.05, therefore, the two independent variables do affect satisfaction while the variables reliability, responsiveness and assurance have a significant number> 0.05. Therefore, the three variables actually do not affect satisfaction. The conclusions in this study are of the five variables tested to see whether giving satisfaction to visitors to the Salatiga city library, it turns out that only two variables that significantly influence the satisfaction variable, both are tangible and empathetic variables.Kata kunci: Tangible, emphaty, reliability, responsiveness, assurance dan kepuasan                     konsumen